Here the Differential equations is given by \(xy+6e^y=6e\) with y(0)=1y(0)=1. Taking differentiate both sides with respect to x we get \((d/dx(xy+6e^y))=(d/dx)6e^y (d/dx(xy)+6(d/dx)e^y=0 y+xy'+(6e^y)y'=0\) From here putting y(0)=1y(0)=1 we get y′(0)=−1/6e. Agin differentiate both sides above expressions with respect to x we get \((d/dx)(y+xy'+(6e^y)y')=0 y'+y'+xy''+(6e^y)y'^2+(6e^y)y''=0\) Now putting x=0x=0 and y(0)=1y(0)=1, y′(0)=−1/6e we get -\((1/3e)-6e(1/36e^2)+6ey''=0 -> 6ey''=1/3e+1/6e -> 6ey''=1/2e -> y''=1/12e^2\)